PELATIHAN PEMBUATAN JAHE BUBUK SEBAGAI PELUANG USAHA BAGI IBU-IBU KARANGKAMAL DESA WINDUNEGARA BANYUMAS - Yahya Ramadhan; Ratri Radhitya Ningrum; Lili Dwi Saraswati; Aida Ayu Faiza Tsania; Rienelda Safa’atun Aisah; Nadira Jinan Ajanti; Alfian Tri Pamuji; Aulia Adelia Wulandari; Alfirsta Auliyamatin Zafithri; Endiyono Endiyono (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
The transition from the dry season to the rainy season can cause a decline in the immune system, making the body more vulnerable to bacterial and viral infections. This condition increases the risk of various diseases that spread more easily with changing weather. Immunity during the rainy season can be strengthened by consuming herbal medicines. Ginger, one of the traditional remedies that has been used for centuries for health, is made from natural ingredients. Herbal medicines containing ginger can be consumed on their own or combined with other herbal remedies to enhance their efficacy.The aim of this program is to provide knowledge and skills in processing instant ginger, which can improve individuals' ability to generate income and develop new flavors for the market. This program uses a practical demonstration method. The participants, especially mothers, were very enthusiastic about following every step of the process, asking questions, and actively participating. Through this training, it is hoped that participants will be able to process ginger into a healthy and beneficial herbal drink.